2012
DOI: 10.3176/eng.2012.1.03
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of technological parameters through response surface methodology in machining hardened X38CrMoV5-1 using whisker ceramic tool (Al2O3+SiC)

Abstract: This experimental study is an attempt to model technological parameters such as cutting forces and surface roughness in hard turning of X38CrMoV5-1 hot work tool steel hardened to 50 HRC. This steel is free from tungsten on Cr-Mo-V basis, insensitive to temperature changes and has a high wear resistance. It is employed for the manufacture of helicopter rotor blades and forging dies. The workpiece is machined by a whisker ceramic tool (insert CC670 of chemical composition 75%Al 2 O 3 +25%SiC) under dry conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…A Box–Behnken central combination design was employed to investigate the influence of three factors, namely silicon carbide mass ratio, reaction temperature, and adhesive dosage, on the response values of the friction coefficient of the fir-based silicon carbide ceramic material (FSCC) [ 36 , 37 , 38 ]. Seventeen experimental combinations (two parallel replications for each experimental combination) were generated at three levels for each factor.…”
Section: Methodsmentioning
confidence: 99%
“…A Box–Behnken central combination design was employed to investigate the influence of three factors, namely silicon carbide mass ratio, reaction temperature, and adhesive dosage, on the response values of the friction coefficient of the fir-based silicon carbide ceramic material (FSCC) [ 36 , 37 , 38 ]. Seventeen experimental combinations (two parallel replications for each experimental combination) were generated at three levels for each factor.…”
Section: Methodsmentioning
confidence: 99%
“…Derakhshan and Akbari [10] explored the effects of independent parameters such as hardness of parts and cutting speeds on the surface quality during CNC turning of AISI 4140 alloy steel with CBN tool. Fnides et al [11] investigated the effect of cutting parameters (cutting speed, feed rate and depth of cut) on surface roughness during hard turning of X38CrMoV5-1 hot work tool steel using a whisker ceramic tool under dry condition and found that the feed rate is the dominant factor for affecting surface roughness, followed by cutting speed. Mandal et al [12] used a central composite design (CCD) based on response surface methodology (RSM) to investigate the machinability of zirconia toughened alumina (ZTA) inserts while turning AISI 4340 steel and they found that cutting speed, depth of cut and the quadratic value of cutting speed have significant effect on the surface roughness.…”
Section: Introductionmentioning
confidence: 98%
“…The analysis of variance ANOVA is a computational technique that enables the estimation of the relative contributions of each of the control factors to the overall measured response. RSM is a collection of mathematical and statistical techniques that are useful for the modelling and analysis of problems in which response of interest is influenced by several variables and the objective is to optimize the response [8][9][10] ].…”
Section: Introductionmentioning
confidence: 99%